ANALISIS PENGGUNAAN ECC PADA SISTEM AUTENTIKASI DI IOT - Purwiko, Daniel Perdana Putra; Dewanta, Favian; Afianti, Farah (MULTINETICS, 2022)
The Internet of Things is a complex system that is widely used in many ways to advance human life. As a result, Internet of Things (IoT) has many security vulnerabilities and requires an authentication system to protect user data. Selecting the authentication type that suits your needs is critical to achieving excellent performance on your Internet of Things (IoT) devices with relatively minimal specifications. Due to this situation, Elliptic Curve Cryptography (ECC) algorithm is one of the recommended algorithms which consumes less resources in the process. This study aims to test and compare the Fiat-Shamir based Elliptic Curve Cryptography (ECC) and Elliptic Curve Diffie-Hellman based Hash Message Authentication Code (ECDH-HMAC) authentication algorithms. Parameters for this test are computation time, delay, program storage, and communication cost of the authentication algorithm. The experimental results show that the Elliptic Curve Diffie-Hellman based Hash Message Authentication Code (ECDH-HMAC) algorithm has the lowest computational time, delay, and program storage usage, and the Fiat-Shamir based Elliptic Curve Cryptography (ECC) algorithm has the lowest communication cost value.